Comparative study of methods for the isolation and purification of bovine kappa-casein and its hydrolysis by chymosin - Coolbear, K P; Elgar, D F; Coolbear, T; Ayers, J S (Journal of dairy research, 1996)
kappa-Casein was purified from a single batch of whole acid casein (kappa-A variant) using different methods in order to compare their merits in producing a purified material with a carbohydrate and phosphate heterogeneity representative of the whole kappa-casein complement in milk. Ion-exchange methods of purification gave products of higher purity than precipitation techniques involving final purification by ethanol fractionation, but all methods resulted in kappa-caseins of apparently similar heterogeneity and chemical composition. The purified kappa-caseins were hydrolysed with chymosin and the derived macropeptides isolated. These were all virtually identical as determined by reversed-phase chromatography and gel electrophoresis. Some observations on chymosin hydrolysis of kappa-casein were made. In addition to formation of the major para-kappa-casein (Glu1-Phe105) and macropeptide (Met106-Val169), chymosin hydrolysis at pH 6.6 also resulted in two minor para-kappa-caseins with N-termini corresponding to Phe18 and Ser33 of kappa-casein. At pH 5.5 and 4.5 para-kappa-casein was rapidly hydrolysed into at least six fragments, one of which had an N-terminus corresponding to Trp76 of kappa-casein. At pH 6.6, 5.5 and 4.5 the kappa-casein macropeptide was stable to chymosin, but at pH 2.3 it was hydrolysed by chymosin into fragments with N-termini corresponding to Met106, Ile125, Ala138, Val139, Thr145 and Glu147 of kappa-casein.